A Comparison of Five Experimental Techniques to Measure Charge Carrier Lifetime in Polymer/Fullerene Solar Cells. Issue 4 (18th October 2014) - Clarke, Tracey M.; Lungenschmied, Christoph; Peet, Jeff; Drolet, Nicolas; Mozer, Attila J.
<x xml:space="preserve">Abstract</x> It is important to accurately measure the charge carrier lifetime, a crucial parameter that influences the collection efficiency in organic solar cells. Five transient and small perturbation experimental techniques that measure charge carrier lifetime are applied to a device composed of the polymer PDTSiTTz blended with the fullerene PCBM: time‐resolved charge extraction (TRCE), transient absorption spectroscopy (TAS), photoinduced charge extraction by linearly increasing voltage (photo‐CELIV), transient photovoltage, and electrochemical impedance spectroscopy. The motivation is to perform a comprehensive comparison of several different lifetime measurement techniques on the same device in order to assess their relative accuracy, applicability to operational devices, and utility in data analysis. The techniques all produce similar charge carrier lifetimes at high charge densities, despite previous suggestions that transient methods are less accurate than small perturbation ones. At lower charge densities an increase in the apparent reaction order is observed. This may be related to surface recombination at the contacts beginning to dominate, or an inhomogeneous charge distribution. A combination of TAS and TRCE appears suitable. TAS enables the investigation of recombination mechanisms at early times since it is not limited by RC (resistance‐capacitance product) or charge extraction losses. Conversely, TRCE is useful particularly at low densities when other mechanisms, such as surface recombination, may occur.